Live-attenuated Pru: Δcdpk2 strain of Toxoplasma gondii protects against acute, chronic and congenital toxoplasmosis - Wang, Jin-Lei; Li, Ting-Ting; Elsheikha, Hany M.; Chen, Kai; Cong, Wei; Yang, Wen-Bin; Bai, Meng-Jie; Huang, Si-Yang; Zhu, Xing-Quan (Oxford University Press, 2018)
Background: The threat of Toxoplasma gondii infection in immunocompromised individuals and pregnant women necessitates the development of a safe and effective vaccine. Here, we examined the immune protection conferred by live-attenuated strain of T. gondii. Methods: We tested the efficacy of intraperitoneal vaccination using 500 Ca2+-dependent protein kinase 2 (cdpk2)-deficient tachyzoites of T. gondii Pru strain against acute, chronic and congenital toxoplasmosis in mice. The kinetics of antibody response, cytokines, and other quantifiable correlates of protection against T. gondii infection were determined. Results: Vaccination with Pru:Δcdpk2 induced a high level of anti-T. gondii IgG titer, Th1 response at 28 days post-vaccination (dpv), and mixed Th1/Th2 response at 70 dpv. All vaccinated mice survived a heterologous challenge with 1000 tachyzoites of RH or ToxoDB#9 (PYS or TgC7) strains. Also, vaccination protected against homologous infection with 20 T. gondii Pru cysts, and improved pregnancy outcome by reducing parasite cyst load in the brain, maintaining litter size and body weight of pups born to vaccinated dams challenged with 10 Pru cysts compared to pups born to unvaccinated dams. Conclusion: The use of T. gondii Pru:Δcdpk2 mutant strain represents a promising approach to protection against acute, chronic and congenital toxoplasmosis in mice.